1998
DOI: 10.1037/0097-7403.24.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Satiation causes within-session decreases in instrumental responding.

Abstract: The amount of food necessary to cause within-session decreases in response rates was investigated by varying reinforcer duration (Experiment 1) and grain size (Experiment 2). Within-session response rates quickly increases to a peak, and the decrease throughout the rest of the session was greater for conditions with larger amounts of food. The decreases were greatest for the pigeons that ate the least when food was freely available. Previous studies of within-session changes in responding are reviewed and rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 59 publications
1
55
0
1
Order By: Relevance
“…Therefore, McSweeney and her colleagues concluded that satiety variables other than habituation affect absolute response rates but contribute little to within-session decreases in responding. Recently, Killeen and his colleagues (Bizo et al, 1998;DeMarse et al, 1999) criticized this conclusion and argued that satiation contributes to within-session decreases. However, all of the results that they present are also compatible with the habituation theory (for more detailed discussion, see McSweeney & Murphy, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, McSweeney and her colleagues concluded that satiety variables other than habituation affect absolute response rates but contribute little to within-session decreases in responding. Recently, Killeen and his colleagues (Bizo et al, 1998;DeMarse et al, 1999) criticized this conclusion and argued that satiation contributes to within-session decreases. However, all of the results that they present are also compatible with the habituation theory (for more detailed discussion, see McSweeney & Murphy, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The first argues that these changes are produced by arousal followed by satiation (Bizo, Bogdanov, & Killeen, 1998; DeMarse, Killeen, & Baker, 1999;Killeen, 1995). According to this satiation hypothesis, as the session progresses, the animal gradually becomes more aroused and then more sated.…”
mentioning
confidence: 99%
“…Debate has been heated on this issue. Although some authors believe that the establishing operation is arousal-satiation (Bizo, Bogdanov, & Killeen, 1998;DeMarse, Killeen, & Baker, 1999;Hinson & Tennison, 1999;Palya & Walter, 1997) Mook (1996) identified factors in the mouth, stomach (e.g., distention), intestine (e.g., cholecystokinin), and liver (e.g., blood sugar level as measured at the liver) as satiety factors for eating. Mook also identified oral stimulation, stomach filling, and cellular hydration as satiety factors for drinking.…”
Section: Changes In Reinforcer Effectiveness Produce Within-session Cmentioning
confidence: 99%
“…Habituation may help to explain the termination of a behavior that is usually attributed to a different variable. For example, if I asked you why you stopped eating (an ingestive behavior), you would probably say that you were full (satiated; e.g., Bizo et al, 1998). If I asked you why you stopped running (an energetic response), you would probably say that you were tired (fatigued; e.g., Belke, 1997).…”
Section: Separating Satiation and Habituationmentioning
confidence: 99%
“…The latter served to examine the reinforcing effects of the cues themselves. The procedures used in these experiments were identical to those used in Experiment 1 with the following exceptions: (1) rats in Experiment 2 received approximately 30 sucrose pellets in their home cage for three days before sucrose reinforcement training in order to familiarize them with the pellets; (2) no surgery was performed on the rats from either experiment; and (3) the training, extinction, and test sessions in both experiments were only 30 min in duration to avoid satiation found with longer training sessions (Bizo et al, 1998) and to attain a comparable number of cue presentations per session as Experiment 1. In addition, rats in Experiment 3 were matched to sucrose rats when they transitioned from food-restriction to ad libitum access in the home cage.…”
Section: Experiments 2 and 3: Reinstatement After Training With Sucromentioning
confidence: 99%